NMDA Receptors in Astrocytes - Verkhratsky, Alexei; Chvátal, Alexandr (Neurochemical research, 2020)
Astrocytes support glutamatergic neurotransmission in the central nervous system through multiple mechanisms which include: (i) glutamate clearance and control over glutamate spillover due to operation of glutamate transporters; (ii) supply of obligatory glutamate precursor glutamine via operation of glutamate-glutamine shuttle; (iii) supply of L-serine, the indispensable precursor of positive NMDA receptors neuromodulator D-serine and (iv) through overall homoeostatic control of the synaptic cleft. Astroglial cells express an extended complement of ionotropic and metabotropic glutamate receptors, which mediate glutamatergic input to astrocytes. In particular a sub-population of astrocytes in the cortex and in the spinal cord express specific type of NMDA receptors assembled from two GluN1, one GluN2C or D and one GluN3 subunits. This composition underlies low Mg2+ sensitivity thus making astroglial NMDA receptors operational at resting membrane potential. These NMDA receptors generate ionic signals in astrocytes and are linked to several astroglial homoeostatic molecular cascades.
Keywords: membránové potenciály; Membrane Potentials; Neurotransmitters; NMDA receptors; Astrocytes; mozková kůra; Animals; lidé; astrocyty; Glutamate; Astrocyte; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Humans; Nerve Net; zvířata; nervová síť; Cerebral Cortex